Shear strengthening of continuous RC T-beams with deep embedded CFRP and steel bars: A numerical study. (June 2023) - Dutta, Baisali; Nath Nayak, Amar; Dirar, Samir; Nanda, Bharadwaj; Theofanous, Marios
Abstract: This paper presents a non-linear finite element parametric study of continuous RC T -beams shear retrofitted with deep embedded (DE) carbon fibre reinforced polymer (CFRP) bars and steel bars. Two-dimensional nonlinear finite element (NLFE) models for these shear-retrofitted beams have been developed and validated with the published literature based on the ultimate shear strength, load versus displacement behaviour, failure mode and strain developed in the longitudinal steel at mid-span. NLFE models of five RC T -beams are developed, out of which one model is for the un-strengthened beam, two are for the shear retrofitted beams with vertical DE bars and the leftover two are for the shear retrofitted with inclined 45° DE bars. Parametric investigations have been conducted to evaluate the impacts of shear span to depth ratio ( a/d ), compressive strength of concrete, effective beam depth and DE bar reinforcement to the existing shear links ratio on the shear strength, load versus deflection behaviour and strain developed in the shear links of these continuous beams. It is found that the above considered parameters of the continuous RC-T beams influence the shear capacity, load–displacement behaviour and strain in the shear link significantly. Moreover, the present work will provide sufficient knowledge to the designers for designing the shear retrofitted RC beams with DE bars.